THE ROLE OF MULTIMEDIA IN THE PROCESS OF TEACHING A FOREIGN LANGUAGE - Juraeva Zamira Ishmuminovna; Akhrorova Mohinur Avaz kyzy (Galaxy International Interdisciplinary Research Journal, 2022)
The given article describes the usage of multimedia and its results during the teaching of foreign languages. Topics were discussed concerning the necessity of using computer technology at the lesson and different methods which lead to receiving information clearly in foreign language, As there written in the article, the most thing is motivation. It means that the teacher should find the student’s interests and student must feel self-confident.